Clinical study of lower respiratory tract infections in children attending a tertiary care hospital - Munagala, Venkata Krishna; Uma Mahesh, Ramisetty M.; Kandati, Jithendra; Ponugoti, Munilakshmi (International Journal of Contemporary Pediatrics, 2017)
Background: WHO estimated burden of respiratory tract infections in 2010, estimates four and half million deaths due to respiratory tract infections among children every year. In India, 1.2 million deaths have been reported among children due to RTI among 5.9 million deaths globally. Lower respiratory tract infections are most common causes of death than upper respiratory tract infections. Pneumonia and Bronchiolitis are most common types of LRTI in children. Pneumonia accounts for most of the deaths in children < 5 years of age. The present study was undertaken with an objective to know the various types of lower respiratory tract infections in children less than 12 years of age. The study also aims to know the various bacterial agents causing respiratory tract infections with their antibiotic susceptibility. Methods: Hospital based, prospective cross-sectional study was conducted for a period of one year and 375 children were enrolled. Demographic, clinical history and examination was done and signs and symptoms noted. All necessary investigations were performed and followed regularly for management and outcome. Results: Incidence of LRTI in the study was 9.76% with male preponderance (65.33%) and most common among children in 1-4 years age group. Ratio of males to females was 1.9:1. 73.6% of cases were in low socio-economic group, 35.2% were found with PEM-I grade and 18.13% had no immunization coverage. Cough and breathlessness were the major symptoms and respiratory distress and clubbing were major signs in the study. Bronchopneumonia was the commonest cause (38.7%) followed by bronchiolitis and Allergic bronchitis. 18.45 of cases had anemia and Leucocytosis was also present. Pulmonary infiltration was the major finding in the X-ray of chest. Streptococcus pneumoniae and Klebsiella pneumoniae were the common bacterial pathogens isolated. Conclusions: To conclude, our study clearly highlighted the various types of clinical presentations, risk factors and different types of LRTI in children <12 years of age. Understanding a clear knowledge of the etiology and bacterial pathogens clearly provides guidance for the physician in management and clinical outcome.